2017
DOI: 10.3168/jds.2016-12111
|View full text |Cite
|
Sign up to set email alerts
|

Apparent ruminal synthesis of B vitamins in lactating dairy cows fed diets with different forage-to-concentrate ratios

Abstract: Effects of the forage-to-concentrate ratio on apparent ruminal synthesis of thiamine, riboflavin, niacin, vitamin B, folates, and vitamin B were evaluated in an experiment using 14 ruminally and duodenally cannulated Holstein cows. The experiment was a crossover design with two 15-d treatment periods and a 14-d preliminary period in which cows were fed a diet intermediate in composition between the treatment diets. Treatments were diets containing low-forage (44.8% forage, 32.8% starch, 24.4% neutral detergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
2
21
0
2
Order By: Relevance
“…In the last decade, several studies also investigated the influence of different types of feed on the ARS of niacin (Table 2). Niehoff et al (14) observed that ARS of niacin was less in cows fed the low concentrate diet compared with the high or medium concentrate diet, which is consistent with the findings of Seck et al (7) In addition, the diet with high niacin content (9,12) would likely result in negative ARS of niacin. Especially, 98•5 % of supplementary nicotinamide (15) and 88-94 % of supplementary nicotinic acid (14) disappeared in the rumen, resulting in a greater negative ARS of niacin.…”
Section: Niacin Sources and Bioavailabilitysupporting
confidence: 69%
See 2 more Smart Citations
“…In the last decade, several studies also investigated the influence of different types of feed on the ARS of niacin (Table 2). Niehoff et al (14) observed that ARS of niacin was less in cows fed the low concentrate diet compared with the high or medium concentrate diet, which is consistent with the findings of Seck et al (7) In addition, the diet with high niacin content (9,12) would likely result in negative ARS of niacin. Especially, 98•5 % of supplementary nicotinamide (15) and 88-94 % of supplementary nicotinic acid (14) disappeared in the rumen, resulting in a greater negative ARS of niacin.…”
Section: Niacin Sources and Bioavailabilitysupporting
confidence: 69%
“…In above-mentioned studies, the difference in half-life time could be another reason for the different content in blood of two niacin vitamers as the blood samples were collected before feeding. However, Campbell et al (24) reported that concentrations of plasma nicotinic acid and plasma (7) ; Schwab et al (8) ; Beaudet et al (9) Alfalfa silage 21•6-291•0 Seck et al (7) ; Castagnino et al (10) ; Castagnino et al (11,12) Orchardgrass silage 52•4-81•7 Castagnino et al (10) ; Castagnino et al (11,12) Grass hay 12•1 Schwab et al (8) Alfalfa hay 34•0-70•2 Schwab et al (8) ; Beaudet et al (9) Wheat straw 46•6 Beaudet et al (9) Soyabean hulls 44•6-228•9 Schwab et al (8) ; Beaudet et al (9) Maize 7•0-30•2 Seck et al (7) ; Schwab et al (8) ; Castagnino et al (10) ; Castagnino et al (11,12) Barley 36•9 Schwab et al (8) Beet pulp 36•9 Beaudet et al (9) Soyabean meal 34•5-58•4 Seck et al (7) ; Schwab et al (8) ; Beaudet et al (9) ; Castagnino et al (10) ; Castagnino et al (11,12) Blood meal 45•2-56•3 Schwab et al (8) ; Castagnino et al (11) nicotinamide did not differ over time in 11 h after 12 g/d of free nicotinic acid or nicotinamide supplementation. Thus, further research are required to clarify the kinetics of niacin, especially RPN, in ruminants.…”
Section: Niacin Sources and Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of dietary carbohydrates on thiamine concentration may be due to its influence on rumen fermentation and the microbial community. Castagnino et al (27) and Seck et al (28) reported a positive correlation between ruminal pH and thiamine AS. The impact of pH on thiamine status may be related to the increasing thiaminase production at low ruminal pH, since pH values below 5•8 (31) are optimal for thiaminase-producing bacteria (C. sporogenes and a few species of Bacillus; Brent & Bartley (32) ), as a result, thiamine degradation by microbial thiaminase increased.…”
Section: Maize Ground 2•1-3•84mentioning
confidence: 95%
“…Schwab et al (7) reported that the average ruminal thiamine AS in lactating dairy cows is 50•6 mg/d, which is similar to the value of 51•7 mg/d reported by Breves et al (2) and >26•0 mg/d reported by Santschi et al (29) . In the recent studies by Beaudet et al (23) , Castagnino et al (27) and Seck et al (28) , the ruminal thiamine AS was negative (from −39•8 to 0•8 mg/d), which they hypothesised was due to thiamine destruction by thiaminase enzymes or degradation by the ruminal microflora. Based on the above studies, we can conclude that dietary Castagnino et al (22) , Schwab et al (7) , Beaudet et al (23) Grass hay 0•89-1•49 Schwab et al (7) , Beaudet et al (23) Maize silage 0•57-1•37 Schwab et al (7) , Beaudet et al (23)…”
Section: Microbial Synthesis Degradation and Absorption Of Thiamine mentioning
confidence: 95%